2016
DOI: 10.1136/bmjgh-2016-000144
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of three feeding regimens for home-based management of children with uncomplicated severe acute malnutrition: a randomised trial in India

Abstract: ObjectiveTo assess the efficacy of ready-to-use therapeutic food (RUTF), centrally produced RUTF (RUTF-C) or locally prepared RUTF (RUTF-L) for home-based management of uncomplicated severe acute malnutrition (SAM) compared with micronutrient-enriched (augmented) energy-dense home-prepared foods (A-HPF, the comparison group).MethodsIn an individually randomised multicentre trial, we enrolled 906 children aged 6–59 months with uncomplicated SAM. The children enrolled were randomised to receive RUTF-C, RUTF-L or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 40 publications
1
74
0
Order By: Relevance
“…The expected consequence of this would be to treat them with a lower RUTF dose, without routine medical treatment, and with a lesser level of medical assessment and follow-up, which may affect treatment outcomes Although currently available evidence on this topic is limited, a RUTF dose meeting total daily nutritional requirements may improve recovery and prevent relapse compared to RUTF given as a supplement to the usual diet [38]. Recent studies involving uncomplicated SAM patients reported important incidence of co-morbidities and referrals to hospital during the treatment period, thereby highlighting the importance of keeping these patients under close medical attention [39,40]. Failure to adequately address comorbidities occurring during outpatient treatment has been highlighted as important risk factors of poor treatment outcomes [41].…”
Section: Discussionmentioning
confidence: 99%
“…The expected consequence of this would be to treat them with a lower RUTF dose, without routine medical treatment, and with a lesser level of medical assessment and follow-up, which may affect treatment outcomes Although currently available evidence on this topic is limited, a RUTF dose meeting total daily nutritional requirements may improve recovery and prevent relapse compared to RUTF given as a supplement to the usual diet [38]. Recent studies involving uncomplicated SAM patients reported important incidence of co-morbidities and referrals to hospital during the treatment period, thereby highlighting the importance of keeping these patients under close medical attention [39,40]. Failure to adequately address comorbidities occurring during outpatient treatment has been highlighted as important risk factors of poor treatment outcomes [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, 40% of children showed no recovery even after 16 weeks of use of RUTF. 33 A Cochrane review published in 2013 (8 randomised controlled trials, 10 037 children) reported that lipid based therapeutic foods and specially formulated foods such as corn-soy blended foods are effective in treatment of moderate acute malnutrition. However, no study evaluated the impact of improving the local diet to increase its nutritional content.…”
Section: How Is It Managed?mentioning
confidence: 99%
“…Meanwhile, the results of a rigorous trial involving supervised feeding with three different types of supplements [including commercial RUTF] have recently been published. This trial suggests that the gains across the arms were transient once the intervention was withdrawn (10,16) The same trial also showed that the difference in efficacy between augmented home foods and commercial RUTF was not significant, while a locally produced RUTF, identical in composition to the commercial RUTF, was inexplicably superior. Regardless of the product, significantly, supervised feeding was required to achieve good outcomes.…”
Section: Some Alternativesmentioning
confidence: 81%
“…While it has taken the cover of 'lack of evidence' as its justification, it has been equally slow to take cognizance of the evidence as it emerges. Rather than creating whatever evidence-base is currently lacking to address the issue of how to empower communities to take charge of the nutrition of their own children better, it is engaged in promoting a reliance on technical, top-down measures of only marginally greater efficacy in the short term (10,13,16). It has also steadfastly refused to recognize the opportunity costs of pushing for an elusive 'cure' at the constant expense of prevention (17,18) and ignored concerns related to impacts upon health in the long term with products like RUTF (14) that are high in sugar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation